Differences between public and private hospitals in complications following catheter ablation of atrial fibrillation: a cohort study in Australia. (25th November 2020) - Ngo, L; Ali, A; Ganesan, A; Woodman, R; McGavigan, A; Adams, R; Ranasinghe, I
Abstract: Background: Comparing outcomes of care between public and private hospitals is critical to inform patients and improve care quality. Purpose: To compare complication rates following catheter ablation of atrial fibrillation (AF) up to 30-days post discharge between public and private hospitals. Methods: We included patients ≥18 years who underwent AF ablation in the Australian states of New South Wales, Queensland, Victoria, and Western Australia from 2010–2015. The primary outcome was the occurrence of any complication up to 30-days after discharge. The association between provider type and the risk of complications was examined using logistic regression with inverse probability of treatment weighting (IPTW) propensity scores to account for differences in measured confounders. The minimum strength of association required for an unmeasured confounder to nullify any observed association was estimated using the E value. Results: We identified 18, 074 AF ablations during the study period (mean age 62.3±11.4y, 28.8% female, 78.4% performed in private hospitals). Patients ablated at public hospitals were younger (59.3 vs. 63.1y, p<0.001) but had higher rates of heart failure (10.3% vs. 7.7%, p<0.001), diabetes (10.9% vs. 7.9%, p<0.001), chronic kidney disease (4.9% vs. 2.2%, p<0.001), and chronic lung diseases (4.2% vs. 3.6%, p=0.046) than those at private hospitals. The unadjusted rate of complications was higher in publics hospitals compared with private ones (7.59% vs. 5.26%, p<0.001). After IPTW, there was good covariate balance with a median standardised difference of 0.006 (range 0.0–0.032) and the adjusted difference in procedural complication rates between two sectors remained significant (OR=1.46, 95% CI 1.24–1.73). The difference was mainly driven by an elevated risk of complications requiring cardiac surgery (OR=3.85, 95% CI 1.35–10.98), acute kidney injury (OR=2.95, 95% CI 1.12–7.74), cardiorespiratory failure (OR=2.69, 95% CI 1.19–6.04), postprocedural infection (OR=2.50, 95% CI 1.28–4.86), and bleeding (OR=1.26, 95% CI 1.02–1.56) (Figure 1). The disparity in the complication rates persisted when in-hospital (OR=1.41, 95% CI 1.16–1.70) and post-discharge (OR=1.52, 95% CI 1.12–2.07) complications were analysed separately. The E value was 1.79, suggesting that the disparity might plausibly be explained by unmeasured confounders. Conclusion: AF ablation at a public hospital was associated with a 46% higher risk of complications compared with ablation at a private hospital, mainly driven by a higher risk of complications requiring cardiac surgery, acute kidney injury, cardiorespiratory failure, infections, and bleeding. The disparity could be due to differences in care quality between two sectors or explained by unmeasured confounders such as higher procedural complexity in public hospitals. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The National Heart Foundation of Australia